A clinical study on microwave ablation of T1N0M0 papillary thyroid carcinoma locating in dangerous region - Hui-di Zhou; Ying Wei; Zhen-long Zhao; Lili Peng; Yan Li; Ming-an Yu (BMC Cancer)
Abstract To evaluate the feasibility, safety and efficiency of the microwave ablation (MWA) of T1N0M0 papillary thyroid carcinoma (PTC) locating in dangerous region. This is a clinical retrospective study, and the data of patients who underwent thermal ablation for T1N0M0 PTC from June 2016 to March 2021 were reviewed. After ablation, the rates of technical success, as well as the changes in tumor size and volume, tumor disappearance, disease progression, and complications, were assessed. According to the tumor size, the patients were divided into T1a and T1b subgroups. There was a total of 94 cases enrolled in the present study. The mean age was 43.06 ± 11.51 years (22–65 years). The median follow-up time was 33 months (25-75% IQR 24–44; 12-85months). The technical success rate was 100%. Due to expanding ablation, the MD and volume of the ablation zone increased at the 1st and 3rd months and decreased from the 12th month after ablation (p < 0.05 for all). At the end of follow-up, the complete disappearance of ablation zone occurred in 78(78/94, 82.98%) cases, including 65 (65/75, 86.67%) cases in T1a subgroup and 13(13/19, 68.4%) cases in the T1b subgroup. There was no difference between the two subgroups (p = 0.121). 5 (5/94,5.3%) patients developed disease progression, and all of them were in T1a subgroup (5/75, 6.67%). There was not significantly different between two subgroups (p = 0.559). The complication rate was 15.96% (15/94). Recurrent laryngeal nerve (RLN) injury encountered in 11 (11/75, 14.7%) cases in the T1a subgroup and 4 (4/19, 21.1%) cases in the T1b subgroup. No significant difference between the two subgroups (p = 0.74). This preliminary study indicates that MWA is an effective treatment for T1N0M0 PTC locating in dangerous region.